Revisit to incremental housing focusing on the role of a comprehensive community centre: the case of Jinja, Uganda. Issue 2 (3rd April 2019) - Park, Joon; Lim, Yirang; Kim, Kyohee; Wang, Hyounggun
ABSTRACT: Incremental housing is a gradual process whereby residents incrementally improve or extend their houses by themselves, whenever funding or time becomes available. This approach has attracted attention as an affordable way of improving poor living conditions in slums often with sites-and-services scheme. In many cases, this approach is coupled with an emphasis on self-help sweat equity, which can be strengthened by active community involvement. This study seeks to suggest a way of combining a scheme of empowering self-reliant communities with incremental housing. Based on the lessons from previous slum upgrade projects in Jinja, Uganda, this study points out the necessity of 1) more sustainable approach with self-help incremental housing than one-time grant-based projects, 2) an assisted way of empowering community and providing training schemes, 3) a temporary shelter for original dwellers who are affected by slum upgrade projects, and 4) an inclusive scheme for tenants who are frequently ignored in many slum upgrade schemes. This study proposes a 'Self-Reliance Centre (SRC)', which is designed to function as a space for community empowerment, a training centre, and a temporary shelter for incremental housing scheme in slum upgrade. As an assisted self-help approach, the SRC in incremental housing has a feature of initial involvement by public sector to invite eventual self-reliance of communities for sustainability in incremental housing.